New data of Nazeris Fauvel from the Dayao Mountains, Guangxi, China (Coleoptera, Staphylinidae, Paederinae) - Ma, Wen-Jing; Miao, Zheng-Yi; Hu, Jia-Yao (Zootaxa, 2021)
Three new species of Nazeris Fauvel, 1873 from the Dayao Mountains, Guangxi, China, are described and illustrated: N. shengtangus Ma, Miao & Hu, sp. n., N. songi Ma, Miao & Hu, sp. n., and N. curvilaminatus Ma, Miao & Hu, sp. n. An identification key to the Nazeris species in Guangxi, and a map showing their distribution are provided.